Environmental nitrite induced ferroptosis and inflammation: Coated sodium selenite alleviated gill damage via SP1/GPX4 signaling in grass carp (Ctenopharyngodon idella) - Fei Zhao; Pei Wu; Weidan Jiang; Hongyun Zhang; Yang Liu; Yaobin Ma; Hongmei Ren; Xiaowan Jin; Yinggu Kuang; Lin Feng; Xiaoqiu Zhou (Aquaculture, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

A reappraisal of the role of just transition in Taiwan’s 2050 net-zero pathway - Anton Ming-Zhi Gao; Jui-Chu Lin; Chien-Te Fan; Tsung Kuang Yeh; Jong-Shun Chen; Chao-Ning Liao (Energy and Climate Change, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Seismic reservoir characterization of deep carbonates under complex overburden: a lithofacies-association zonation workflow, Longwangmiao Formation, Sichuan Basin - Lei Tan; Yuanzhi Zhou; Junliang Li; Linzhi Zhang; Ya Zhang; Pingchao Fang; Minzhi Zhang; Bowen Liu; Longyan Yin; Lin Qiao; Mingzhi Kuang; Hong Liu (Carbonates and Evaporites, 2026)

C–N–H chemistry, PAH growth and soot formation in non-premixed flames of ethylene/ammonia/hydrogen: A CFD study - Anurag Dahiya; Zi-Jia Wang; Kuang C. Lin (Fuel, 2026)

Broad-specificity antibody profiled by hapten prediction for immunoassay development of anilinopyrimidine fungicides - Shiqi Lin; Liqiang Liu; Yingyue Zhu; Shanshan Song; Hua Kuang; Chuanlai Xu; Lingling Guo (Food Chemistry, 2026)

New insight on designing docetaxel prodrug liposomes with high stability and intelligent release: Length-like or structure-like modification strategy - Si Zheng; Danping Wang; Zhiyu Kuang; Shengyao Xu; Wenxiao Li; Haiyu Zhao; Jingyi Zhang; Weiyao Li; Zhonggui He; Jin Sun; Lin Li; Bingjun Sun (Chemical Engineering Journal, 2026)

Polymer-dependent accumulation of PFASs on microplastics in Xiamen Bay: field evidence and laboratory partitioning - Haitao Lin; Weiming Kuang; Jincheng Sun; Rupeng Du; Weiming Wu; Zhuoyun Chen; Liang Wang; Zhong Pan (Water Research, 2026)

Betanodavirus induces RIPK3/MLKL-mediated necroptosis and IL-21/adaptive immune response via superoxide stress/mTOR/ULK1-mediated autophagy signal in the context of brain damage in grouper (Epinephelus coioides) - Hong-Jun Liao; Kuang-Wen Chen; Hsing-Ni Lin; Pei-Cih Gong; Jen-Leih Wu; Jiann-Ruey Hong (Fish & Shellfish Immunology, 2026)

Molecular Insights into Phenolic Polymerization during the Transition from High-Valent Iron Oxidation to Electron Transfer - Hai Kuang; Ruike Men; Jianying Wu; Lin Li; Yinhao Dai; Peiren Ding; Lushi Lian; Hongyu Dong; Xiaohong Guan (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Irregular-wave transformation over an open-top artificial reef with low-opening-ratio baffles under variable relative submergence - Hongyi Li; Cuiping Kuang; Jiadong Fan; Jilong Chen; Xin Cong; Lin Li (Ocean Engineering, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Spatiotemporal dual-network assessment of land-use carbon metabolism in Hubei Province: An integrated ENA-SNA framework - Xuehan Lin; Chengliang Liu; Lu Zhang; Bing Kuang; Qingsong He (Applied Geography, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Targeting eIF5A2 hypusination with bikinin sensitizes hepatocellular carcinoma to lenvatinib by suppressing TFEB-mediated autophagy - Shuqian Wang; Qingyun Zhou; Qiaomei Lin; Shufen Zhang; Ying Cai; Fangnan Wu; Fangyuan Kuang; Lianghui Wang; Shangzhi Xie; Jiahua Lan; Li Zheng; Guodong Xu; et al. (Human Cell, 2026)

Robot-assisted laser osteotomy system based on dose–effect model-guided feedforward control - Zeng Kuang; Yanping Lin; Shiqi Peng; Yinwei Li; Huifang Zhou (Medical & Biological Engineering & Computing, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Nitrite-induced muscle endoplasmic reticulum and mitochondrial contact disturbance in grass carp (Ctenopharyngodon idella): Alleviating effects of coated sodium selenite - Fei Zhao; Pei Wu; Weidan Jiang; Hongyun Zhang; Yang Liu; Yaobin Ma; Hongmei Ren; Xiaowan Jin; Yinggu Kuang; Lin Feng; Xiaoqiu Zhou (Aquaculture, 2026)

Spectral energy redistribution and wave attenuation performance of an ecological trapezoidal submerged breakwater under irregular waves - Cuiping Kuang; Weibo Wang; Hongyi Li; Lin Li; Guihui Zhong; Chao Shen (Ocean Engineering, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Trophic transfer in a cold seep food web: Dual constraints from δ13C-δ15N isotopes and rare earth elements - Zice Jia; Niu Li; Xun Sun; Shamik Dasgupta; Shaomin Lin; Hongfei Lai; Wenhua Feng; Chao Zhong; Zenggui Kuang; Fang Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

Consistent neural evidence to support novelty and appropriateness processing for creative thinking: a coordinated meta-analysis using activation likelihood estimation - Jiabao Lin; Yuanyun He; Siying Zhang; Lei Mo; Changyi Kuang; Yajue Chen (Brain Structure and Function, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

An integrated framework for early detection and transmissibility assessment of emerging variants in wastewater - Xingwen Chen; Tin Phan; Wei Lin Lee; Katie Clark; Steven F. Rhode; Samantha Brozak; Bruce Pell; Tsultrim Palden; Mats Leifels; Anna Gitter; Yang Kuang; Stefan Wuertz; et al. (International Journal of Hygiene and Environmental Health, 2026)

A new Rhizomucor miehei lipase immobilized on anhydride-hydrophobized amino supports: Optimization, characterization and application in preparing medium- and long-chain structured lipids - Yiyi Lin; Xiansi Gao; Zheling Zeng; Di Kuang; Kai Fang; Tianyi Song; Ping Yu; Deming Gong; Cheng Zeng; Xianghui Yan (Food Bioscience, 2026)

Litter inputs reshape soil respiration partitioning in subalpine forests: Pivotal role of microbial gene abundance and root-microbe interactions - Yuxiao Kuang; Jia Xiong; Linhui Zhang; Genxu Wang; Zhaoyong Hu; Wenzhi Wang; Juying Sun; Ruiying Chang; Xiangyang Sun; Yuanyuan Su; Shan Lin; Hailong Sun; et al. (Agricultural and Forest Meteorology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

MnO2-functionalized membrane with enhanced demulsification and antifouling performance for stable oil-in-water emulsion separation - Sudong Yang; Zhiying He; Mei Zhu; Junjie Zheng; Yixuan Kuang; Hongyi Li; Xueting Yuan; Qing Xu; Qian Zhang; Peng Zhao; Jianmin Luo; Lin Chen (Journal of Environmental Chemical Engineering, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Changes in quality properties and cell wall polysaccharides metabolism of Chinese olives during chilling injury development - Yunman Chen; Xiaoyong Kuang; Ziyao Lin; Zhenlu Huang; Guixia Huang; Zhongqi Fan; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

Colletotrichum species associated with anthracnose of Camellia oleifera in Jiangxi Province, China - Weigang Kuang; Wenna Gao; Liangpeng Wan; Yimei Li; Yachun Lin; Xugen Shi; Lianhu Zhang; Ruqiang Cui (Physiological and Molecular Plant Pathology, 2026)

Collagen type XV regulation via MMP2-dependent degradation governs ovarian development in the rice stem borer, Chilo suppressalis - Yue Li; Suijie Kuang; Yan Tang; Zhuotian Yao; Yechen Pan; Ziren Zang; Yang Cui; Hongshuai Gao; Lin Qiu; Yansong Xiao; Tin Liu; Qi Su; et al. (Insect Biochemistry and Molecular Biology, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Low temperature delays longan pulp breakdown through DlMYB108-DlPME17 transcriptional regulation - Qiu-yi Ye; Zhong-qi Fan; Wei Shan; Jian-fei Kuang; Jian-ye Chen; Wang-jin Lu; Hui Wang; Hetong Lin; Wei Wei (Postharvest Biology and Technology, 2026)

A new strategy of urine stabilization via in situ electrochemical acidification: Enabled by CeMn-doped cobalt spinel anode - Qi Kuang; Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Ying Chen; Yuan Liu (Journal of Environmental Chemical Engineering, 2026)

Has rising bottom water temperature since the Last Glacial Maximum caused gas hydrate dissociation? - Cong Cheng; Tao Jiang; Zenggui Kuang; Zigui Chen; Jinfeng Ren; Hongfei Lai; Licheng Cao; Qianru Wang; Yipan Hu; Lin Song; Chen Liang; Xu Zhao; et al. (Global and Planetary Change, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

CFD data-driven CNN-LSTM for fast prediction of instantaneous flow characteristics in hydrocyclones - Dianyu E; Yuhao Zhang; Hongwei Hu; Guangtai Xu; Lin Liu; Jiaxin Cui; Cong Tan; Ruiping Zou; Shibo Kuang (Minerals Engineering, 2026)

Experimental study of flame height and merging condition of jet fire arrays - Yujie Lin; Yuhang Chen; Guanlin Peng; Chen Kuang; Jiang Lv; Chang Qi; Anfeng Yu; Yi Liu (Fuel, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

Two new phenylethanol glycosides from the roots of eleutherococcus senticosus (rupr. et maxim.) maxim - Jia-Tong Wu; Ke Xiao; Hao-Lin Yang; Hui-Chen Zhu; Si-Yi Wang; Juan Pan; Meng-Meng Li; Wei Guan; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2025)

Low-altitude remote sensing and deep learning-based canopy detection method for the navigation of orchard unmanned ground vehicles - Yongda Lin; Xiaofei Song; Weiming Xiao; Dongdong Kuang; Shiyu Xia; Honggen Chang; Supakorn Wongsuk; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2025)

MaWRKY45 mediates H2S-mitigated chilling injury in banana fruit by coordinating with MaERF53L/121L - Zengxiang Lin; Danling Cai; Zongli Liu; Zixin Lin; Wei Wei; Wei Shan; Jianye Chen; Wangjin Lu; Xinguo Su; Jianfei Kuang (Postharvest Biology and Technology, 2025)

The in-flight cooling of ballistic pyroclasts during mafic explosive eruptions: a numerical model - Chiedozie C. Ogbuagu; Kuang C. Lin; Thomas J. Jones; Silvio De Angelis (Journal of Volcanology and Geothermal Research, 2025)

AdaptVFMs-RSCD: Advancing Remote Sensing Change Detection from binary to semantic with SAM and CLIP - Wandong Jiang; Yuli Sun; Lin Lei; Gangyao Kuang; Kefeng Ji (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Detecting changes without comparing images: Rules induced change detection in heterogeneous remote sensing images - Yuli Sun; Lin Lei; Zhang Li; Gangyao Kuang; Qifeng Yu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Transcription factor E93 regulates vitellogenesis via the vitelline membrane protein 26Ab gene in Chilo Suppressalis - Siyang Chen; Yingjuan Sun; Suijie Kuang; Yan Tang; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Hongshuai Gao; Youzhi Li; Lin Qiu (Molecular Biology Reports, 2025)

Luteolin modulates liver macrophage subtype polarization and play protective role in sepsis induced acute hepatic injury - Liangyong Deng; Qiulei Yu; Gang Kuang; Liuyang Wang; Jing Fan; Lin Ye (Inflammation Research, 2025)

Mango MiEIL4 modulates starch degradation during fruit ripening by upregulating the expression of β-amylase and α-amylase genes - Zilong Zhou; Baijun Li; Zengxiang Lin; Wei Zhong; Wei Wei; Wei Shan; Jianye Chen; Wangjin Lu; Chaojie Wu; Jianfei Kuang (Postharvest Biology and Technology, 2025)

Optimization of coagulation process and its influence on membrane fouling for Anaerobic-Anoxic-Oxic-Anoxic Membrane Bioreactor (A2OA-MBR) - Xiaoping Tan; Ke Kuang; Jie Li; Caijing Lai; Zebin Chen; Ziyuan Wang; Wei Song; Yi Wu; Dachao Lin; Xing Du (Journal of Environmental Sciences, 2025)

Geophysical monitoring technology and simulation in CO2 geological storage: A comprehensive review - Wenke Tang; Wuqin Li; Zitian Lin; Jun Zhu; Siyao Zhou; Yangmin Kuang; Yanpeng Zheng (Gas Science and Engineering, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

Identification and semi-quantification of alkylated polycyclic aromatic hydrocarbons in PM2.5 filter samples using in-injection port thermal desorption coupled with two-dimensional gas chromatography and rapid-scanning quadrupole mass spectrometry (TD-GC×GC-qMS) - Manfei Lin; Yongming Feng; Xiao He; Bin-Yu Kuang; X.H. Hilda Huang; Yongmei Liang; Jian Zhen Yu (Atmospheric Pollution Research, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Assessment for seawall modifications to mitigate land crabs roadkills from field experiments and agent-based modeling - Kuang-Yu Tseng; Yun-Ting Hsieh; Yu-Wen Chen; Ting-Yu Liang; Hui-Chen Lin (Journal of Environmental Management, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Local synergistic collaboration between metallic Bi clusters, oxygen vacancies, and Cu atom enhances the electrochemical CO2-to-CH4 performance of CuO nanocatalysts - Yu-Chiao Tseng; Shih-Hsuan Chen; Kuang-Yi Liu; Yen-Lin Lai; Shu-Yu Lee; Chia-Shing Wu; Kuan-Wen Wang; Tsan-Yao Chen (Chemical Engineering Journal, 2025)

High-performance and robust 3D perovskite solar cells enabled by self-assembled amphiphilic molecules - Chao-Yun Lin; Guan-Lin Chen; Kuang-Hao Cheng; Syang-Peng Rwei; Hsiao-Chi Hsieh; Leeyih Wang (Chemical Engineering Journal, 2025)

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Seaweed polysaccharides as potential Prebiotics: Rationale, factors, Prebiotic activity manifestations, gut health mechanisms and extraintestinal impacts - Qianmin Lin; Li Zhong; Mei Zeng; Supaluck Kraithong; Xuewei Xia; Weiyang Kuang; Qingqing Wang; Riming Huang (Trends in Food Science & Technology, 2025)

Identifying risk factors for methotrexate-induced acute kidney injury despite full prevention in patients with primary central nervous system lymphoma - Wen-Ying Lin; Chun-Kuang Tsai; Chiu-Mei Yeh; Chia-Jen Liu (Toxicology and Applied Pharmacology, 2025)

Identification of heavy metal transport-related genes and microRNAs in response to cadmium toxicity and micronutrient deficiency in barley roots - Liuhui Kuang; Jian Chen; Jie Ding; Tao Yan; Fei Gao; Lin Li; Zhigang Han; Dezhi Wu (Journal of Hazardous Materials, 2025)

Synergistic enhancement of alkaloid biosynthesis in Catharanthus roseus CMCs via enzyme Inhibition and abiotic elicitation - Haihua Li; Jiahe Li; Ningjin Liu; Huishan Li; Jiarui Wang; Rulan Zhang; Jingyan Xue; Xiaotian Kang; Xinying Guan; Shiya Lin; Ziyu Zhang; Jiaqi Kuang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

YOLO-CMST: Towards accurate pineapple flowering induction using YOLO-based models with the Cross Multi-Style Translator - Kuang-Yueh Pan; Wan-Ju Lin; Jian-Wen Chen; Yi-Hong Lin (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

MaWRKY21 is involved in ethylene-mediated cold tolerance in banana fruit by regulating ROS accumulation - Ya-Na Chen; Shu-Qin Lin; Wen Song; Wei Wei; Wei Shan; Jian-Fei Kuang; Jian-Ye Chen; Wang-Jin Lu (Postharvest Biology and Technology, 2025)

Doublesex knockout via CRISPR/Cas9 disrupts fertility and sexual dimorphism of wings in the rice stem borer, Chilo suppressalis - Yatao Zhu; Suijie Kuang; Zhuotian Yao; Yingjuan Sun; HongShuai Gao; Qiao Gao; Wenbing Ding; HuaLiang He; Youzhi Li; Lin Qiu (Insect Biochemistry and Molecular Biology, 2025)

A new phenylpropanoid glycoside from the aerial parts of Saposhnikovia divaricata (Turcz.) Schischk. and its chemotaxonomic significance - Zhenqiang Liu; Yan Pan; Yan Sun; Yuxuan Lin; Shuang Liu; Qian Zhang; Juan Pan; Wei Guan; Haixue Kuang; Anam Naseem; Yan Liu; Bingyou Yang (Biochemical Systematics and Ecology, 2025)

Overexpression of GPX4 in diabetic rat kidney alleviates renal injury induced by ferroptosis - Keping Wu; Enyi Zhu; Jiasi Chen; Qingyan Kuang; Jiawen Lin; Shuping Zhao; Xiaochang Xu; Shuping Li; Yuan Sui; Mingcheng Huang; Yimin Zhang (BioMetals, 2025)

Experimental and Numerical Study on the Temperature Rise Characteristics of Multi-Layer Winding Non-Metallic Armored Optoelectronic Cable - Shanying Lin; Xihong Kuang; Yujie Zhang; Gen Li; Wenhua Li; Weiwei Shen (Journal of Marine Science and Engineering, 2025)
The non-metallic armored optoelectronic cable (NAOC) serves as a critical component in deep-sea scientific winch systems. Due to its low density and excellent corrosion resistance, it has been widely adopted in marine exploration. However, as the operational water depth increases, the NAOC is subjected to multi-layer winding on the drum, resulting in a cumulative temperature rise that can severely impair insulation performance and compromise the safety of deep-sea operations. To address this issue, this paper conducts temperature rise experiments on NAOCs using a distributed temperature sensing test rig to investigate the effects of the number of winding layers and current amplitude on their temperature rise characteristics. Based on the experimental results, an electromagnetic thermal multi-physics field coupling simulation model is established to further examine the influence of these factors on the maximum operation time of the NAOC. Finally, a multi-variable predictive model for maximum operation time is developed, incorporating current amplitude, the number of winding layers, and ambient temperature, with a fitting accuracy of 97.92%. This research provides theoretical and technical support for ensuring the safety of deep-sea scientific operations and improving the reliability of deep-sea equipment.

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Application and mechanism of Co3O4/Co(OH)2 heterojunctions as matrices for small molecules detection by MALDI-TOF MS - Zufeng Qiu; Kexin Yang; Zijian Huang; Hongsheng Zhao; Zhiwei Lin; Qin Kuang; Zhaoxiong Xie (Journal of Hazardous Materials, 2025)

Antiviral activity of epicatechin against Singapore grouper iridovirus in vitro and in vivo - Lin Huang; Jihui Kuang; Jieying Yu; Qing Yu; Weiqiang Xu; Mingzhu Liu; Yunyi Wei; Shuyu Han; Yanhua Huang; Pengfei Li (Fish & Shellfish Immunology, 2025)

Electrical Resistivity Tomography Methods and Technical Research for Hydrate-Based Carbon Sequestration - Zitian Lin; Qia Wang; Shufan Li; Xingru Li; Jiajie Ye; Yidi Zhang; Haoning Ye; Yangmin Kuang; Yanpeng Zheng (Journal of Marine Science and Engineering, 2025)
This study focuses on the application of electrical resistivity tomography (ERT) for monitoring the growth process of CO2 hydrate in subsea carbon sequestration, aiming to provide technical support for the safety assessment of marine carbon storage. By designing single-target, dual-target, and multi-target hydrate samples, convolutional neural networks (CNNs), recurrent neural networks (RNNs), and residual neural networks (ResNets) were constructed and compared with traditional image reconstruction algorithms (e.g., back-projection) to quantitatively analyze ERT imaging accuracy. The experiments used boundary voltage as the input and internal conductivity distribution as the output, employing the relative image error (RIE) and image correlation coefficient (ICC) to evaluate algorithmic performance. The results demonstrate that neural network algorithms—particularly RNNs—exhibit superior performance compared to traditional image reconstruction methods due to their strong noise resistance and nonlinear mapping capabilities. These algorithms significantly improve the edge clarity in target identification, enabling the precise capture of the hydrate distribution during carbon sequestration. This advancement effectively enhances the monitoring capability of CO2 hydrate reservoir characteristics and provides reliable data support for the safety assessment of hydrate reservoirs.

Genetic Diversity in Three Sinipercine Fishes Based on Mitochondrial D-Loop and COX1 Sequences - Minghui Lin; Xu-Fang Liang; Ke Lu; Ming Zeng; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi), golden mandarin fish (Siniperca scherzeri), and Coreoperca whiteheadi are three important aquaculture species in China facing several threats to their production. Genetic diversity was assessed by sequencing the mitochondrial D-loop and cox1 regions in 207 individuals across nine populations. The genetic diversity analysis, based on the concatenated sequences, revealed that the total haplotype diversity was high across all sinipercine fish populations. Population differentiation analysis revealed that most genetic variation was within populations: 74.5% in S. chuatsi (p

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

P2Y6R Inhibition Induces Microglial M2 Polarization by Promoting PINK1/Parkin-Dependent Mitophagy After Spinal Cord Injury - Jiezhao Lin; Yuanfang Sun; Haoran Huang; Cheng Yu; Wenhao Kuang; Yihan Wang; Lixin Zhu (Molecular Neurobiology, 2025)

Progress in using cross-linking technologies to increase the thermal stability of colloidal delivery systems - Wen Xu; Kuang He; Ziqiang Lin; David Julian McClements; Zhengyu Jin; Long Chen (Critical Reviews in Food Science and Nutrition, 2025)

Recent advances in enzymatic modification techniques to improve the quality of flour-based fried foods - Guifang Huang; David Julian McClements; Kuang He; Ziqiang Lin; Zipei Zhang; Ruojie Zhang; Zhengyu Jin; Long Chen (Critical Reviews in Food Science and Nutrition, 2025)

Antibiotics inhibit nitrogen removal and promote greenhouse gas emissions in high-density earthworm-enhanced constructed wetlands - Guangqian Kuang; Huijuan Cao; Xiangyong Zheng; Yishi Lin; Xingmin Jin; Min Zhao; Wenjuan Han (Journal of Water Process Engineering, 2025)

Iron-modified activated carbon enhanced Anammox-n-DAMO progress in granular sludge: Performance and microbial mechanism - Tao Wang; Ziyang Lin; Baowen Zhang; Chuanlin Cai; Bin Kuang; Liying Deng (Desalination, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The system design of high-throughput miniature software-defined radio as a Ka/K-band communication payload for CubeSats - Kuan Po Chiu; Cissi Ying-tsen Lin; Yih-Min Chen; Jui-Hong Chou; Chi-Kuang Chao; Tiger J.-Y. Liu (Advances in Space Research, 2025)

The Deep Space Radiation Probe: Development of a first lunar science payload for space environment studies and capacity building - Loren C. Chang; Wei-Yi Lin; Yi-Hsuan Chou; Jen-Siang Lin; Chieh Lung; I. Chen; Kai-Jie Hou; Glenn Franco Gacal; Yi-Chung Chiu; Yushun Wang; Hui-Hui Chou; Chi-Kuang Chao; et al. (Advances in Space Research, 2025)

Risk assessment of potentially toxic elements, microplastics, and microorganisms in groundwater around municipal solid waste landfill - Xueya Li; Tianmu Peng; Linyi Lin; Muhammad Amjad Khan; Shurui Zhang; Meijuan Kuang; Jinming Lou; Jiaxin He; Pangxiang Zhang; Xiaomao Song; Xu Wang; Qing Huang (Journal of Hazardous Materials, 2025)

Sodium hydrosulfide application induces chilling tolerance in banana fruits by enhancing antioxidant gene expression through the upregulation of the ethylene response factors MaERF53L/121L - Zengxiang Lin; Wei Wei; Danling Cai; Wei Shan; Jianye Chen; Yingying Yang; Jia Si; Wangjin Lu; Guohui Zhu; Chaojie Wu; Jianfei Kuang (Food Chemistry, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

The plant retromer components SNXs bind to ATG8 and CLASP to mediate autophagosome movement along microtubules - Yanglan Liao; Xibao Li; Wenlong Ma; Xinyi Lin; Jiayi Kuang; Xuanang Zheng; Zien Li; Fanfan Qiao; Chuanliang Liu; Jun Zhou; Faqiang Li; Ruixi Li; et al. (Molecular Plant, 2025)

Mitochondrial alterations and signatures in hepatocellular carcinoma - Tsung-Hsien Chen; Shu-Hsien Lin; Ming-Yang Lee; Hsiang-Chen Wang; Kun-Feng Tsai; Chu-Kuang Chou (Cancer and Metastasis Reviews, 2025)

Dietary lysine deficiency causes intestinal immune dysfunction partially via Janus kinases (JAKs)/signal transducers and activators of transcription (STATs) signalling pathways of on-growing grass carp (Ctenopharyngodon idella) - Yangyang Hu; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Shengyao Kuang; Ling Tang; Lu Zhang; Haifeng Mi; Xiaoqiu Zhou (Animal Feed Science and Technology, 2025)

The characteristics and potential transport trajectory of epimicroplastic red tide species in the Taiwan Strait - Conghui Peng; Kang Wang; Hui Lin; Shunyang Chen; Xu Dong; Yahui Gao; Baohong Chen; Fangfang Kuang (Frontiers in Marine Science, 2025)
Due to the carrier’s role of microplastics, attached microalgae may be transported further, posing a threat to marine ecosystems, especially those red tide species. By combining the investigated results of Dongshan Bay and Quanzhou Bay with the simulation of transport trajectories using the Lagrangian particle tracking model, this study systematically investigated the characteristics and transport trajectories of epimicroplastic red tide species. Based on the investigations of Dongshan Bay and Quanzhou Bay respectively in summer of 2022, the characteristics of epimicroplastic red tide species were learned. Results showed that totally 13 red tide species were found in two bays, with 6 species in Dinophyta, 5 species in Diatom, 1 species in Ochrophyta and 1 species in Cyanophyta respectively. Also, the potential transport trajectories of epimicroplastic species were simulated to study their effect to the ecological environment of the surrounding waters. According to the simulated transport trajectories, those species could be transported further by microplastics while some particles would be obstructed during these three-month processes. During the transport processes, epimicroplastic red tide species from two bays would influence three provinces, which have high records of red tide outbreak in China. This study firstly combined models to investigate the potential transport trajectory of epimicroplastic red tide species, providing insights into the mechanisms of red tide outbreak.

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Evidence of lower age, fast growth, and shrinking habitat in critically endangered croaker fish Larimichthys crocea - Chien-Hsiang Lin; Tai-Yan Lin; Aafaq Nazir; Yen-Chun Wang; Pei-Ling Wang; Yoshiyuki Iizuka; Kuang-Ti Li; Ming-Tsung Chung; Jen-Chieh Shiao (Estuarine, Coastal and Shelf Science, 2025)

Insomnia in Parkinson’s Disease: Causes, Consequences, and Therapeutic Approaches - Xiaoyu Duan; Hanshu Liu; Xinyu Hu; Qinwei Yu; Guiying Kuang; Long Liu; Shurui Zhang; Xinyi Wang; Jingwen Li; Danfang Yu; Jinsha Huang; Tao Wang; et al. (Molecular Neurobiology, 2025)

Corrigendum to “Soybean glycinin impaired immune function and caused inflammation associated with PKC-ζ/NF-κb and mTORC1 signaling in the intestine of juvenile grass carp (Ctenopharyngodon idella)” [Fish and Shellfish Immunol. 106 (2020) 393–403] - Ya-Lin Zhang; Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

A multi-omics approach reveals low temperature inhibition of flavones and flavonols accumulation in postharvest bananas via downregulation of MabHLH363 - Wen Song; Shu-Qin Lin; Qi Yin; Tian-He Liu; Lin-Zhi Gan; Jian-Ji Qi; Ying-Ying Yang; Wei Wei; Wei Shan; Jian-Fei Kuang; Jian-Ye Chen; Wang-Jin Lu (Postharvest Biology and Technology, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Microbial community succession and changes of volatile compounds in the fermentation process of bamboo shoots - Jinmei Wei; Zongjun Li; Jinyan Kuang; Zikang Yan; Li Wang; Ying Lin; Jin Du; Ke Li; Yuanliang Wang; Li Yang (Food Microbiology, 2024)

A ZnO-nanorod/PEDOT:PSS nanocomposite functionalized bridge-like membrane type nanomechanical sensing device for ultrasensitive blood lead detection - Yi-Kuang Yen; Chia-Ming Yang; Chen-Ting Kao; Tzung-Hai Yen; Ragurethinam Shanmugam; Yan-Lin Chen; Hwai-En Lin (Analytica Chimica Acta, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

High water resistance starch based intelligent label for the freshness monitoring of beverages - Yun Wang; David Julian McClements; Zipei Zhang; Ruojie Zhang; Kuang He; Ziqiang Lin; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Jianwei Zhao; Zhengyu Jin; et al. (Food Chemistry, 2024)

Research status and prospects of CO2 geological sequestration technology from onshore to offshore: A review - Zitian Lin; Yangmin Kuang; Wuqin Li; Yanpeng Zheng (Earth-Science Reviews, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Crustal-mantle layering deposits in the Von Kármán crater, South Pole-Aitken basin - Zhi Zhong; Yuqi Qian; Chenglong Li; Alexander Y. Sun; Zhongxian Cai; Lei Lin; Xu Guo; Yanbin Kuang; Shiqi Wen; Long Xiao (Earth and Planetary Science Letters, 2024)

Machine learning for subsurface geological feature identification from seismic data: Methods, datasets, challenges, and opportunities - Lei Lin; Zhi Zhong; Chenglong Li; Andrew Gorman; Hao Wei; Yanbin Kuang; Shiqi Wen; Zhongxian Cai; Fang Hao (Earth-Science Reviews, 2024)

Self-Healing fluorinated polymer deep eutectic electrolytes for stable lithium metal batteries - Yingzhi Yu; Canhui Ling; Jixu Yang; Antai Zhu; Tuoya Naren; Yuxin Chen; Yuejiao Chen; Weifeng Wei; Xiaobo Ji; Chengchao Li; Libao Chen; Lin Mei; et al. (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Fractionation, spatial distribution, ecological and health risk assessment of cobalt and nickel in surface sediment of a bay along the southeast coast of China - Yang Liu; Weiming Kuang; Xiuwu Sun; Weili Wang; Cai Lin; Hui Lin (Marine Pollution Bulletin, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Colorimetric detection of furin based on enhanced catalytic activity of G-quadruplex/hemin DNAzyme - Liu Shi; Lin Wang; Xiaomeng Yu; Deqi Kuang; Yue Huang; Nana Yang; Jie Yang; Genxi Li (Analytica Chimica Acta, 2024)

Machine learning prediction on wetland succession and the impact of artificial structures from a decade of field data - Kuang-Yu Tseng; Yun-Ting Hsieh; Hui-Chen Lin (Science of The Total Environment, 2024)

Energy and proline metabolisms participate in the occurrence of chilling injury in cold-stored Chinese olive fruit - Guo Chen; Xiaoyong Kuang; Zhongqi Fan; Yazhen Chen; Yifen Lin; Hui Wang; Yihui Chen; Hetong Lin (Postharvest Biology and Technology, 2024)

An effective preserving strategy for strawberries by constructing pectin/starch coatings reinforced with functionalized eggshell fillers - Hao Xu; Yihao Huang; Kuang He; Ziqiang Lin; David Julian McClements; Yao Hu; Hao Cheng; Xinwen Peng; Zhengyu Jin; Long Chen (Food Chemistry, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

A novel identification model for rock burst grades-taking Jinping II hydropower station hub engineering as an example - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu (Computers and Geotechnics, 2024)

Rational design of Bacteria-Targeted and Photo-Responsive MOF gel with antibacterial and anti-inflammatory function for infected wound healing - Qiao-Tong He; Peipei Qian; Xin-Yi Yang; Qiancheng Kuang; Yue-Ting Lin; Wei Yi; Tianzhao Tian; Yue-Peng Cai; Xu-Jia Hong (Chemical Engineering Journal, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Low temperature downregulates MabHLH355 and its associated target genes responsible for scavenging ROS in banana peel under cold stress - Shu-Qin Lin; Wen Song; Lin-Zhi Gan; Wei Wei; Wei Shan; Jian-Fei Kuang; Jian-Ye Chen; Wang-Jin Lu (Postharvest Biology and Technology, 2024)

Battery recycling models selection and contractual incentives: From an information sharing perspective - Lin Feng; Mengru Qu; Adolf K.Y. Ng; Peng Jia; Haibo Kuang (Journal of Cleaner Production, 2024)

Review of formation mechanisms and quality regulation of chewiness in staple foods: Rice, noodles, potatoes and bread - Guifang Huang; David Julian McClements; Kuang He; Zipei Zhang; Ziqiang Lin; Zhenlin Xu; Yidong Zou; Zhengyu Jin; Long Chen (Food Research International, 2024)

Recent progress in the hydrophobic modification of starch-based films - Ziqiang Lin; Hao Cheng; Kuang He; David Julian McClements; Zhengyu Jin; Zhenlin Xu; Man Meng; Xinwen Peng; Long Chen (Food Hydrocolloids, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

Electrospun nanofibers-derived functional scaffolds for cancer therapy - Gaizhen Kuang; Xiang Lin; Jinbo Li; Weijian Sun; Qingfei Zhang; Yuanjin Zhao (Chemical Engineering Journal, 2024)

Banana MabZIP21 positively regulates MaBAM4, MaBAM7 and MaAMY3 expression to mediate starch degradation during postharvest ripening - Hong Xu; Lisha Zhu; Zengxiang Lin; Wei Wei; Yingying Yang; Jia Si; Wei Shan; Jianye Chen; Wangjin Lu; Jianfei Kuang; Chaojie Wu (Postharvest Biology and Technology, 2024)

Electrochemical oxidation processes based on renewable energy towards carbon neutrality: Oxidation fundamentals, catalysts, challenges and prospects - Yan Yan; Bing Lin; Liehui Zhang; Yingying Wang; Hailong Zhang; Hongpeng Zheng; Taigang Zhou; Yingqing Zhan; Zongxue Yu; Yun Kuang; Junlei Tang (Chemical Engineering Journal, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Environmental characteristics and major factors controlling chlorophyll a in three seamounts in the Subtropical Western Pacific Ocean - Sun Xiuwu; Ji Xianbiao; Peng Conghui; Lin Cai; Zhou Kaiwen; Lin Hui; Wang Kang; Lin Liru; Kuang Fangfang; Chen Jinmin; Chen Baohong (Regional Studies in Marine Science, 2024)

Alternation of social behaviors for zebrafish (Danio rerio) in response to acute cold stress - Sian-Tai Liu; Chun-Yung Chang; Kuang-Yung Lee; Sok-Keng Tong; Han-Liang Huang; Hsi Chen; Jiun-Lin Horng; Ming-Yi Chou (Fish Physiology and Biochemistry, 2024)

Residues of Polycyclic Aromatic Hydrocarbons in Breast Milk Collected from Jinhua (China) and the Influence of Exercise Habit: Levels and the Potential Health Effects - Qianfeng He; Xiaoge Zhang; Lihong Kuang; Haotian Xu; Yizhong Hou; Fangqu Huang; Zeqiong Xu; Hongjie Sun; Wenjing Deng; Hongjun Lin; Huachang Hong (Exposure and Health, 2024)

Variability and distribution of nighttime equatorial to mid latitude ionospheric irregularities and vertical plasma drift observed by FORMOSAT-5 Advanced Ionospheric Probe in-situ measurements from 2017 – 2020 - Loren C. Chang; Yueh-Chun Hsieh; Chi-Kuang Chao; Yi Duann; Cornelius Csar Jude H. Salinas; Jann-Yenq Liu; Charles C.H. Lin (Advances in Space Research, 2024)

Post-stroke Chinese pure alexia: linguistic features and neuropsychological profiles - Shen-yi Kuang; Yi Xu; Yu-yuan Wang; Zi-gao Wang; Qiang Dong; Xiang Han; Shi-Lin Yang (Acta Neurologica Belgica, 2024)

Expressing a human RNA demethylase as an assister improves gene-editing efficiency in plants - Mengyan Bai; Wenxin Lin; Chunyan Peng; Peizhe Song; Huaqin Kuang; Jieni Lin; Jieping Zhang; Jiyao Wang; Bo Chen; Huarong Li; Fanjiang Kong; Guifang Jia; et al. (Molecular Plant, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Similarity and dissimilarity relationships based graphs for multimodal change detection - Yuli Sun; Lin Lei; Zhang Li; Gangyao Kuang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

GPIC: A set of high-efficiency CUDA Fortran code using gpu for particle-in-cell simulation in space physics - Qiyang Xiong; Shiyong Huang; Zhigang Yuan; Bharatkumar Sharma; Lvlin Kuang; Kui Jiang; Lin Yu (Computer Physics Communications, 2024)

Global change progressively increases foliar nitrogen–phosphorus ratios in China's subtropical forests - Yuan Lai; Songbo Tang; Hans Lambers; Peter Hietz; Wenguang Tang; Frank S. Gilliam; Xiankai Lu; Xianzhen Luo; Yutong Lin; Shu Wang; Feiyan Zeng; Qi Wang; et al. (Global Change Biology, 2024)
Globally increased nitrogen (N) to phosphorus (P) ratios (N/P) affect the structure and functioning of terrestrial ecosystems, but few studies have addressed the variation of foliar N/P over time in subtropical forests. Foliar N/P indicates N versus P limitation in terrestrial ecosystems. Quantifying long‐term dynamics of foliar N/P and their potential drivers is crucial for predicting nutrient status and functioning in forest ecosystems under global change. We detected temporal trends of foliar N/P, quantitatively estimated their potential drivers and their interaction between plant types (evergreen vs. deciduous and trees vs. shrubs), using 1811 herbarium specimens of 12 widely distributed species collected during 1920–2010 across China's subtropical forests. We found significant decreases in foliar P concentrations (23.1%) and increases in foliar N/P (21.2%). Foliar N/P increased more in evergreen species (22.9%) than in deciduous species (16.9%). Changes in atmospheric CO 2 concentrations (), atmospheric N deposition and mean annual temperature (MAT) dominantly contributed to the increased foliar N/P of evergreen species, while , MAT, and vapor pressure deficit, to that of deciduous species. Under future Shared Socioeconomic Pathway (SSP) scenarios, increasing MAT and would continuously increase more foliar N/P in deciduous species than in evergreen species, with more 12.9%, 17.7%, and 19.4% versus 6.1%, 7.9%, and 8.9% of magnitudes under the scenarios of SSP1‐2.6, SSP3‐7.0, and SSP5‐8.5, respectively. The results suggest that global change has intensified and will progressively aggravate N–P imbalance, further altering community composition and ecosystem functioning of subtropical forests.

Enhanced membrane fouling by microplastics during nanofiltration of secondary effluent considering secretion, interaction and deposition of extracellular polymeric substances - Dachao Lin; Caijing Lai; Xiaokai Wang; Zhihong Wang; Ke Kuang; Ziyuan Wang; Xing Du; Lifan Liu (Science of The Total Environment, 2024)

DEM study on the effect of pore characteristic on single particle crushing behavior of porous particles - Du-min Kuang; Zhi-lin Long; Ikechukwu Ogwu; Feng-lan Kuang; Ling-ming Yang (Computers and Geotechnics, 2024)

Focused recharge enhances soil carbon leakage and carbonate weathering in groundwater: Implications for subsurface carbon sinks - Xin Dai; Aimin Liao; Yueqing Xie; Chuan Wang; Xingxing Kuang; Jin Lin; Jichun Wu (Applied Geochemistry, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Combined effects of microcystin-LR and rice straw-derived biochar on the hepatic antioxidant capacity of zebrafish: Insights from LC-MS/MS-based metabolomics analysis - Wang Lin; Kang Ouyang; Ya He; Hui Yang; Yu Kuang; Dapeng Li; Li Li (Science of The Total Environment, 2023)

Effects of vitamin D and zinc deficiency in acute and long COVID syndrome - Kuang-Yu Chen; Chin-Kuo Lin; Ning-Hung Chen (Journal of Trace Elements in Medicine and Biology, 2023)

First report of Serratia marcescens causing seed necrosis on Nelumbo nucifera in China - Weigang Kuang; Xin Gong; Yachun Lin; Lanlan Chen; Xinwen Zheng; Jiping Tang; Xugen Shi; Xiaotang Sun; Lianhu Zhang; Ruqiang Cui (Crop Protection, 2023)

The role of respiratory metabolism in chilling injury development of Chinese olive fruit during cold storage - Bingling Sun; Xiaoyong Kuang; Hetong Lin; Mengshi Lin; Yazhen Chen; Lingzhen Zeng; Yifen Lin; Yihui Chen; Hui Wang; Zhongqi Fan (Postharvest Biology and Technology, 2023)

Modulating covalent organic frameworks with accessible carboxyl to boost superior extraction of polar nitrobenzene compounds from matrix-complicated beverages - Suxin Zhou; Yixin Kuang; Hongkai Lin; Juan Zheng; Gangfeng Ouyang (Food Chemistry, 2023)

Molecular and functional characterization of viperin in golden pompano, Trachinotus ovatus - Lin Huang; Xiaowen Zhu; Jihui Kuang; Bohuan Li; Qing Yu; Mingzhu Liu; Bingzheng Li; Hui Guo; Pengfei Li (Fish & Shellfish Immunology, 2023)

Salt tide affecting algae-laden micropolluted surface water treatment and membrane performance based on BDD electro-oxidation coupled with ceramic membrane process - Xing Du; Bingxuan Li; Zhongjian Zhuang; Ke Kuang; Wei Song; Dachao Lin; Caixia Fu; Zhihong Wang (Environmental Research, 2023)

The Relationship Between Cortical Morphological and Functional Topological Properties and Clinical Manifestations in Patients with Posttraumatic Diffuse Axonal Injury: An Individual Brain Network Study - Fuqing Zhou; Lin Wu; Long Qian; Hongmei Kuang; Jie Zhan; Jian Li; Gerald L. Cheung; Aimin Ding; Honghan Gong (Brain Topography, 2023)

Phytoplankton community structure and environmental factors during the outbreak of Crown-of-Thorns Starfish in Xisha Islands, South China Sea - Conghui Peng; Kang Wang; Wei Wang; Fangfang Kuang; Yahui Gao; Ronggen Jiang; Xiuwu Sun; Xu Dong; Baohong Chen; Hui Lin (Environmental Research, 2023)

Marine Collision Avoidance Route Planning Model for MASS Based on Domain-Based Predicted Area of Danger - Chao-Wei Lu; Chao-Kuang Hsueh; Yung-Lin Chuang; Ching-Ming Lai; Fuh-Shyong Yang (Journal of Marine Science and Engineering, 2023)
When the own ship encounters target ships in a close-quarter situation, an officer on watch needs to safely and timely alter the course of the vessel to avoid a collision. If ECDIS can automatically collect the navigation parameters and plot areas of collision as quasi-static obstruction areas, it will be much easier for seafarers to implement effective route planning. Hence, this study focuses on developing the MCARP model as a theoretical concept based on the DPAD model and LCD model. By operating the MCARP using ArcGIS, DPADs and several effective collision avoidance routes can be generated and imported into ECDIS based on AIS information at large scales and ample time. The graphic overlay of DPADs and effective routes on ECDIS can serve as a collision avoidance strategy reference for the personnel controlling maritime autonomous surface ships. Finally, different ships encountering situations were input into a Transas navigational simulator. The simulation results showed that own ship could avoid collisions with multiple target ships at distances larger than the preset collision avoidance distances, which also indicated that MCARP is practically feasible.

Can port systems be enhanced by government promotion? The case of port cooperation along the maritime silk road - Lin Feng; Xiaodong Li; Adolf K.Y. Ng; Peng Jia; Haibo Kuang; Xingxing Zhang (Ocean & Coastal Management, 2023)

Comprehensive analyses of membrane lipids and phenolics metabolisms reveal the developments of chilling injury and browning in Chinese olives during cold storage - Xiaoyong Kuang; Yazhen Chen; Hetong Lin; Han Lin; Guo Chen; Yifen Lin; Yihui Chen; Hui Wang; Zhongqi Fan (Food Chemistry, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Exploring the effects of livelihood capital on clean cooking of rural households in the Tibetan region of China - Xin Qiu; Jianjun Jin; Chenyang Zhang; Dan Liu; Lin Li; Foyuan Kuang (Energy and Buildings, 2023)

Potential ecological risks of heavy metals and Cd accumulation characteristics of Suaeda salsa under different Cd input and water logging conditions in the Yellow River estuary, China - Hongli Song; Lin Kuang; Lizhi Wang; Wanni Yu; Yuanzhi Wu; Juan An; Xiyuan Wu (Environmental Science and Pollution Research, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Characterization, source identification, risk assessment of potentially toxic elements (PTEs) in the surface water and sediment of the Beibu Gulf, China - Yang Liu; Ronggen Jiang; Weiming Kuang; Cai Lin; Xiuwu Sun; Jinmin Chen; Zhong Pan (Marine Pollution Bulletin, 2023)

Parental food neophobia, feeding practices, and preschooler’s food neophobia: A cross-sectional study in China - Cuiting Yong; Xiaoni Kuang; Yan Liu; Caihong Xiang; Yue Xi; Jiaqi Huo; Jiajing Liang; Hanshaung Zou; Qian Lin (Appetite, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

DNA barcoding identification of IUCN Red listed threatened species in the genus Aquilaria (Thymelaeaceae) using machine learning approaches - Yuexia Lin; Tingting Feng; Jiangpeng Dai; Qiaozhen Liu; Yiming Cai; Jiarong Kuang; Zhaoyu Wang; Xiaoxia Gao; Shaofeng Liu; Shuang Zhu (Phytochemistry Letters, 2023)

Iron-modified biochar boosts anaerobic digestion of sulfamethoxazole pharmaceutical wastewater: Performance and microbial mechanism - Zhili Ni; Lilin Zhou; Ziyang Lin; Bin Kuang; Gefu Zhu; Jianbo Jia; Tao Wang (Journal of Hazardous Materials, 2023)

High temperature elevates carotenoid accumulation of banana fruit via upregulation of MaEIL9 module - Lisha Zhu; Wei Shan; Danling Cai; Zengxiang Lin; Chaojie Wu; Wei Wei; Yingying Yang; Wangjin Lu; Jianye Chen; Xinguo Su; Jianfei Kuang (Food Chemistry, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

DNA barcoding authentication of Uncaria species using machine learning approaches - Qiaozhen Liu; Yiming Cai; Jiangpeng Dai; Jiarong Kuang; Tingting Feng; Xiaoxia Gao; Yuexia Lin; Shuang Zhu (Acta Physiologiae Plantarum, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Association between blood metal exposures and hyperuricemia in the U.S. general adult: A subgroup analysis from NHANES - Yuxuan Tan; Yingyin Fu; Feng Huang; Lin Wen; Xueqiong Weng; Huojie Yao; Huanzhu Liang; Mincong Kuang; Chunxia Jing (Chemosphere, 2023)

Performance and application of a novel drainage anti-slide pile on accumulation landslide with a chair-like deposit-bedrock interface in the Three Gorges Reservoir area, China - Shi-lin Luo; Da Huang; Jian-bing Peng; Ailifeila Aierken; Zhao Li; Xi-bin Kuang; Roberto Tomás (Computers and Geotechnics, 2023)

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Alleviation of hypoxia stress induced oxidative damage, endoplasmic reticulum stress (ERS) and autophagy in grass carp (Ctenopharyngodon idellu) by TTO (Melaleuca alternifolia essential oil) - Ruoying Hu; Shiyu Wang; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Xiaowan Jin; Shengyao Kuang; Ling Tang; Lu Zhang; Xiaoqiu Zhou (Aquaculture, 2023)

Compound Probiotic Ameliorates Acute Alcoholic Liver Disease in Mice by Modulating Gut Microbiota and Maintaining Intestinal Barrier - Haixia Liu; Xing Kang; Xiaodan Yang; Hao Yang; Xiaoyu Kuang; Peng Ren; Huan Yan; Xiaorong Shen; Yongbo Kang; Lin Li; Xiaohui Wang; Linzhi Guo; et al. (Probiotics and Antimicrobial Proteins, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Assessment of factors affecting the diurnal variations of atmospheric PAHs based on a numerical simulation - Zhongxiu Zhen; Yan Yin; Haowen Zhang; Jingyi Li; Jianlin Hu; Lin Li; Xiang Kuang; Kui Chen; Honglei Wang; Qingyuan Yu; Xin Zhang (Science of The Total Environment, 2023)

Banana MaERF124 negatively modulates carotenoid accumulation during fruit ripening through repression of carotenogenesis genes - Danling Cai; Hong Xu; Zongli Liu; Nanhui Chen; Lisha Zhu; Zengxiang Lin; Chaojie Wu; Wei Shan; Jianye Chen; Wangjin Lu; Lin Chen; Jianfei Kuang (Postharvest Biology and Technology, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Circ_0074027 regulates the progression of non-small cell lung cancer via miR-1304-5p/GJB2 axis - Jie Zhang; Yangli Zhu; Ya Lin; Yuli Hu; Zhijian Kuang (Molecular & Cellular Toxicology, 2023)

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

The particle fluxes in sediment traps from Niulang Guyot area in the Northwest Pacific Ocean - Xiuwu Sun; Jinmin Chen; Baohong Chen; Cai Lin; Yang Liu; Jiang Huang; Zhong Pan; Kaiwen Zhou; Qing He; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Nutrient distributions and nitrogen-anomaly (N*) in the tropical North Pacific Ocean - Aiqin Han; Yu Wang; Yunlong Huo; Cai Lin; Kaiwen Zhou; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Shallow-water hydrothermal vent system as an extreme proxy for discovery of microbiome significance in a crustacean holobiont - Ling Chiu; Min-Chen Wang; Kuang-Yu Tseng; Chih-Lin Wei; Huei-Ting Lin; Shan-Hua Yang; Yung-Che Tseng (Frontiers in Marine Science, 2022)
The shallow-water hydrothermal vent (HV) system off Kueishan Island lies at the end of the Okinawa Trough to the northeast of Taiwan. Near its submarine vent openings, aperiodic vent discharges generate a dynamic acidic (pH 5.5-8.1) and sulfidic (9-3000 μM) ecosystem. The dominant metazoan in this unique environment is the brachyuran vent crab, Xenograpsus testudinatus , which has developed robust metabolic strategies and highly adaptive acid-base regulatory mechanisms to maintain its physiological homeostasis. X. testudinatus is considered a holobiont, but the symbiotic mechanisms underlying acid and sulfur tolerance in the host-microbe system remain largely unclear. In this study, we used LoopSeq long-read sequencing of the full-length 16S rRNA gene to identify the bacterial communities present in the gills and carapace surface of X. testudinatus . The alpha diversity analysis, Venn diagram, and principal coordinate analysis (PCoA) indicated that the gills and carapace surface exhibit different bacterial constituents. Further measurements of relative abundance, coupled with functional predictions and fluorescence in situ hybridization (FISH), revealed a predominance of Sulfurovum sp. NBC37-1, a key bacterium that can perform sulfur and hydrogen oxidation to support denitrification processes. Consequently, our findings suggest that the symbiotic bacteria may play a critical role in conferring the extraordinary acid and sulfur tolerances of X. testudinatus , allowing the crustacean holobiont to thrive in its ecological niche within one of the most extreme marine habitats on Earth.

Ginsenoside Rb3 attenuates skin flap ischemia-reperfusion damage by inhibiting STING-IRF3 signaling - Yuanbin Li; Haifen Liu; Zhaohui Zeng; Hui Lin; Xin Chen; Xianglian Yuan; Jizhe Qiu; Fengchun Fu; Zhuang Chen; Jianjun Kuang (Journal of Molecular Histology, 2022)

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Phosphorus fertilization affects soybean rhizosphere phosphorus dynamics and the bacterial community in karst soils - Jihui Tian; Xing Lu; Qianqian Chen; Xizhi Kuang; Cuiyue Liang; Lansheng Deng; Dongjiao Lin; Kunzheng Cai; Jiang Tian (Plant and Soil, 2022)

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

Climatic and edaphic variables determine leaf C, N, P stoichiometry of deciduous Quercus species - Yutong Lin; Yuan Lai; Songbo Tang; Zhangfen Qin; Jianfeng Liu; Fengfeng Kang; Yuanwen Kuang (Plant and Soil, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Phylogeographic structure and population demography of the leopard mandarin fish (Siniperca scherzeri) in the Pearl River drainage - Minghui Lin; Xufang Liang; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Environmental Biology of Fishes, 2022)

Pollution characteristics, mechanism of toxicity and health effects of the ultrafine particles in the indoor environment: Current status and future perspectives - Muhammad Ubaid Ali; Siyi Lin; Balal Yousaf; Qumber Abbas; Mehr Ahmed Mujtaba Munir; Audil Rashid; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2022)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Association between exposure to road traffic noise and hearing impairment: a case-control study - Tang-Chuan Wang; Ta-Yuan Chang; Richard S. Tyler; Bing-Fang Hwang; Yi-Hung Chen; Che-Ming Wu; Chiu-Shong Liu; Kuang-Chao Chen; Chia-Der Lin; Ming-Hsui Tsai (Journal of Environmental Health Science and Engineering, 2021)

Vagus nerve stimulation in pediatric patients with failed epilepsy surgery - Jeng-Dau Tsai; Pi-Chuan Fan; Wang-Tso Lee; Pi-Lien Hung; Kun-Long Hung; Huei-Shyong Wang; Kuang-Lin Lin (Acta Neurologica Belgica, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

Collapsin response mediator protein 5 (CRMP5) modulates susceptibility to chronic social defeat stress in mice - Yu-Fen Lin; Kao Chin Chen; Yen Kuang Yang; Ya-Hsin Hsiao (Molecular Neurobiology, 2021)

Emission sources and full spectrum of health impacts of black carbon associated polycyclic aromatic hydrocarbons (PAHs) in urban environment: A review - Muhammad Ubaid Ali; Lin Siyi; Balal Yousaf; Qumber Abbas; Rashida Hameed; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

Experimental and numerical study on the fragmentation mechanism of a single calcareous sand particle under normal compression - Du-min Kuang; Zhi-lin Long; Rui-qi Guo; Tao Zhao; Kai Wu (Bulletin of Engineering Geology and the Environment, 2021)

Different effects of canopy and understory nitrogen addition on soil organic carbon and its related processes in a subtropical forest - Xiaofei Lu; Wendan Ren; Enqing Hou; Songbo Tang; Lingling Zhang; Zhanfeng Liu; Yongbiao Lin; Shenglei Fu; Dazhi Wen; Yuanwen Kuang (Journal of Soils and Sediments, 2021)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Hyperphosphorylation Renders Tau Prone to Aggregate and to Cause Cell Death - Mengyu Liu; Dexin Sui; Thomas Dexheimer; Stacy Hovde; Xiexiong Deng; Kuang-Wei Wang; Hsin Lian Lin; Hsiao-Tien Chien; Hye Kyong Kweon; Nora Sheen Kuo; Christopher A. Ayoub; Daniela Jimenez-Harrison; et al. (Molecular Neurobiology, 2020)

Upregulation of miR-133a-3p in the Sciatic Nerve Contributes to Neuropathic Pain Development - Lin-Li Chang; Hung-Chen Wang; Kuang-Yi Tseng; Miao-Pei Su; Jaw-Yuan Wang; Yi-Ta Chuang; Yi-Hsuan Wang; Kuang-I Cheng (Molecular Neurobiology, 2020)

Morphological and physiological variations of Cyclocarya paliurus under different soil water capacities - Ying Feng; Xiulian Lin; Lianwen Qian; Nengjing Hu; Chunfeng Kuang; Xiaofeng Li; Zheng Li; Liangrui Huang; Mingming Liu (Physiology and Molecular Biology of Plants, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Structure Elucidation and Mechanistic Study of a New Dimeric Degradant in Ropinirole Hydrochloride Extended-Release Tablets - Zijian Kuang; Tianpei Huang; Dan Li; Danna Zhao; Jianyang Jin; Jinsheng Lin; Wenquan Zhu; Wenbin Chen; Min Li; Weiyang Shen (Pharmaceutical Research, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

EDNRB Reverses Methylprednisolone-Mediated Decrease in Neural Progenitor Cell Viability via Regulating PI3K/Akt Pathway and lncRNA Expression - Shiyuan Li; Ming Zeng; Lin Yang; Jianqi Yang; Jianshao Tan; Hongye Guan; Manyuan Kuang (Journal of Molecular Neuroscience, 2020)

Enzyme-treated soy protein supplementation in low protein diet improved flesh tenderness, juiciness, flavor, healthiness, and antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) - Yan Song; LiangChao Yan; WeiDan Jiang; WeiWei Xiao; Lin Feng; Pei Wu; Yang Liu; ShengYao Kuang; Ling Tang; XiaoQiu Zhou (Fish Physiology and Biochemistry, 2020)

Spatiotemporal assessment of mortality attributable to ambient PM2.5 exposure in Taiwan during 2008–2015 - Su-Lun Hwang; Yu-Ching Lin; Kuang-Yu Hsiao; Chieh-Mo Lin; Miao-Ching Chi (Air Quality, Atmosphere & Health, 2020)

Antimicrobial and cytotoxic juglones from the immature exocarps of Juglans mandshurica - Qin Yang; Qing-Shou Yao; Yi Kuang; Yue-Zhi Zhang; Ling-Ling Feng; Lu Zhang; Lin Guo; Ze-Ping Xie; Shu-Min Zhang (Natural Product Research, 2019)

Correlation between shear strength and soil physicochemical properties of different weathering profiles of the non-eroded and collapsing gully soils in southern China - Bifei Huang; Ming Qiu; Jinshi Lin; Jialin Chen; Fangshi Jiang; Ming-kuang Wang; Hongli Ge; Yanhe Huang (Journal of Soils and Sediments, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

New lignan from the rattan stems of Schisandra chinensis - Bing-You Yang; Zhang-Lin Chen; Yan Liu; Jiang-Tao Guo; Hai-Xue Kuang (Natural Product Research, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Age- and gender-related differences of CPAP acceptance for obstructive sleep apnea syndrome in Taiwan - Yi-Chih Huang; Chou-Chin Lan; Yao-Kuang Wu; Wen-Lin Su; Mei-Chen Yang (Sleep and Biological Rhythms, 2018)

Effects of fine particulate matter and its constituents on emergency room visits for asthma in southern Taiwan during 2008–2010: a population-based study - Su-Lun Hwang; Yu-Ching Lin; Chieh-Mo Lin; Kuang-Yu Hsiao (Environmental Science and Pollution Research, 2017)

A CRISPR/Cas9 toolkit for efficient targeted base editing to induce genetic variations in rice - Bin Ren; Fang Yan; Yongjie Kuang; Na Li; Dawei Zhang; Honghui Lin; Huanbin Zhou (Science China Life Sciences, 2017)

Development of a regulatable expression system for the functional study of Vibrio vulnificus essential genes - Yan-Jiao Zhang; Guozhong Chen; Huiyuan Lin; Pan Wang; Baozhi Kuang; Jing Liu; Shiyong Chen (Antonie van Leeuwenhoek, 2017)

miRNA Expression Change in Dorsal Root Ganglia After Peripheral Nerve Injury - Hsueh-Ling Chang; Hung-Chen Wang; Yi-Ta Chunag; Chao-Wen Chou; I-Ling Lin; Chung-Sheng Lai; Lin-Li Chang; Kuang-I Cheng (Journal of Molecular Neuroscience, 2017)

A novel method to harvest Chlorella sp. by co-flocculation/air flotation - Haiyang Zhang; Zhe Lin; Daoyong Tan; Chunhua Liu; Yali Kuang; Zhu Li (Biotechnology Letters, 2017)

Low-Cost High-Accuracy QRS Detection for Body Area Network Applications - Kuang-Hao Lin; Jen-Hao Wu (Journal of Medical and Biological Engineering, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

The climatic impacts of land use and land cover change compared among countries - Jiyuan Liu; Quanqin Shao; Xiaodong Yan; Jiangwen Fan; Jinyan Zhan; Xiangzheng Deng; Wenhui Kuang; Lin Huang (Journal of Geographical Sciences, 2016)

Complete genome sequence of the cold-active bacteriophage VMY22 from Bacillus cereus - Kunhao Qin; Benxu Cheng; Shengting Zhang; Nan Wang; Yuan Fang; Qi Zhang; Anxiu Kuang; Lianbing Lin; Xiuling Ji; Yunlin Wei (Virus Genes, 2016)

Paraquat Induces Cell Death Through Impairing Mitochondrial Membrane Permeability - Chuen-Lin Huang; Chih-Chang Chao; Yi-Chao Lee; Mei-Kuang Lu; Jing-Jy Cheng; Ying-Chen Yang; Vin-Chi Wang; Wen-Chang Chang; Nai-Kuei Huang (Molecular Neurobiology, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Mitigation of cadmium and arsenic in rice grain by applying different silicon fertilizers in contaminated fields - Hong-Yan Wang; Shi-Lin Wen; Peng Chen; Lu Zhang; Kuang Cen; Guo-Xin Sun (Environmental Science and Pollution Research, 2016)

Isolation and Characterization of the Lytic Cold-Active Bacteriophage MYSP06 from the Mingyong Glacier in China - Mingyuan Li; Jilian Wang; Qi Zhang; Lianbing Lin; Anxin Kuang; Luis Alberto Materon; Xiuling Ji; Yunlin Wei (Current Microbiology, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Characterisation of oligosaccharides from Baizhu by HILIC-MS - Zhe Lin; Yan-Fang Liu; Yang Qu; Li-Ying Shi; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Fractional Thermolysis by Bipolar Radiofrequency Facilitates Cutaneous Delivery of Peptide and siRNA with Minor Loss of Barrier Function - Woan-Ruoh Lee; Shing-Chuan Shen; Chi-Kuang Sun; Ibrahim A. Aljuffali; Shih-Yun Suen; Yin-Ku Lin; Jhi-Joung Wang; Jia-You Fang (Pharmaceutical Research, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Erosion Resistance of HPTRM Strengthened Levee from Combined Wave and Surge Overtopping - Lin Li; Yi Pan; Farshad Amini; Kuang Cuiping; Jean-Louis Briaud (Geotechnical and Geological Engineering, 2014)

Evidences for B6C3-Tg (APPswe/PSEN1dE9) Double-Transgenic Mice Between 3 and 10 Months as an Age-Related Alzheimer’s Disease Model - Zhiyong Zhong; Lin Yang; Xiansheng Wu; Wei Huang; Jiarong Yan; Shenglai Liu; Xia Sun; Ke Liu; Huangquan Lin; Shaosong Kuang; Xiaojiang Tang (Journal of Molecular Neuroscience, 2014)

Investigating the interactive mechanisms between surface water and groundwater over the Jhuoshuei river basin in central Taiwan - Fi-John Chang; Cheng-Hsien Lin; Kuang-Chih Chang; Yu-Hsuan Kao; Li-Chiu Chang (Paddy and Water Environment, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Spectral and functional studies on siphonaxanthin-type light-harvesting complex of photosystem II from Bryopsis corticulans - Wenda Wang; Xiaochun Qin; Min Sang; Dongqin Chen; Kebin Wang; Rongchen Lin; Congming Lu; Jian-Ren Shen; Tingyun Kuang (Photosynthesis Research, 2013)

On brain activity mapping: insights and lessons from Brain Decoding Project to map memory patterns in the hippocampus - Joe Z. Tsien; Meng Li; Remus Osan; GuiFen Chen; LongNian Lin; Phillip Lei Wang; Sabine Frey; Julietta Frey; DaJiang Zhu; TianMing Liu; Fang Zhao; Hui Kuang (Science China Life Sciences, 2013)

A low-pH medium in vitro or the environment within a macrophage decreases the transcriptional levels of fimA, fimZ and lrp in Salmonella enterica serovar Typhimurium - Ke-Chuan Wang; Yuan-Hsun Hsu; Yi-Ning Huang; Ter-Hsin Chen; Jiunn-Horng Lin; Shih-Ling Hsuan; Maw-Sheng Chien; Wei-Cheng Lee; Kuang-Sheng Yeh (Journal of Biosciences, 2013)

Distribution and temporal trend of polybrominated diphenyl ethers in one Shanghai municipal landfill, China - Kai Huang; Jie Guo; Kuang-fei Lin; Xiao-yu Zhou; Jun-xia Wang; Peng Zhou; Feng Xu; Mei-Lan Zhang (Environmental Science and Pollution Research, 2013)

Aberrant methylation and loss expression of RKIP is associated with tumor progression and poor prognosis in gastric cardia adenocarcinoma - Wei Guo; Zhiming Dong; Yanli Guo; Xinwen Lin; Zhifeng Chen; Gang Kuang; Zhibin Yang (Clinical & Experimental Metastasis, 2013)

Dynamics of cadmium concentration in contaminated rice paddy soils with submerging time - Jang-Hung Huang; Shan-Li Wang; Jhin-Hao Lin; Yue-Ming Chen; Ming-Kuang Wang (Paddy and Water Environment, 2013)

Biogeochemical cycling of ferric oxyhydroxide affecting As partition in groundwater aquitard - Sheng-Wei Wang; Chen-Wuing Liu; Kuang-Liang Lu; Li-Hung Lin (Environmental Geochemistry and Health, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

The Hungtsaiping landslides: from ancient to recent - Kuang-Tsung Chang; Ming-Lang Lin; Jia-Jyun Dong; Chang-Hai Chien (Landslides, 2012)

Assessing Taiwan’s energy security under climate change - Shih-Mo Lin; Jun-Chiang Feng; Fu-Kuang Ko (Natural Hazards, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Geomagnetic anomaly at Lunping before the 1999 Chi-Chi earthquake (M w = 7.6) in Taiwan - Kuang-Jung Chen; Bonbbon Chiu; Jee-Shiang Wang; Cheng-Yu Lee; Cheng-Horng Lin; Kevin Chao (Natural Hazards, 2011)

Gene inactivation in the citrus pathogenic fungus Alternaria alternata defect at the Ku70 locus associated with non-homologous end joining - Nan-Yi Wang; Siwy Ling Yang; Ching-Hsuan Lin; Kuang-Ren Chung (World Journal of Microbiology and Biotechnology, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Analysis of forest damage caused by the snow and ice chaos along a transect across southern China in spring 2008 - Quanqin Shao; Lin Huang; Jiyuan Liu; Wenhui Kuang; Jia Li (Journal of Geographical Sciences, 2011)

Cellular Responses Required for Oxidative Stress Tolerance, Colonization, and Lesion Formation by the Necrotrophic Fungus Alternaria alternata in Citrus - Ching-Hsuan Lin; Siwy Ling Yang; Kuang-Ren Chung (Current Microbiology, 2011)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

High-Altitude Adaptation of Yak Based on Genetic Variants and Activity of Lactate Dehydrogenase-1 - Liangde Kuang; Yucai Zheng; Yaqiu Lin; Yaou Xu; Suyu Jin; Yuping Li; Feng Dong; Zhongyong Jiang (Biochemical Genetics, 2010)

Metal Concentrations in Sediments of the Tamsui River, Flows Through Central Metropolitan Taipei - Dong-Shang Lai; Jye-Bin Lin; Wen-Shan Liu; Lung-Kwang Pan; Kuang-Hua Chu; Chien-Yi Chen; Ding-Bang Lin (Bulletin of Environmental Contamination and Toxicology, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Numerical simulations of flow motion and deposition characteristics of granular debris flows - Der-Guey Lin; Sen-Yen Hsu; Kuang-Tsung Chang (Natural Hazards, 2009)

The timing of re-institution of good blood glucose control affects apoptosis and expression of Bax and Bcl-2 in the retina of diabetic rats - Xin-Yuan Gao; Hong-Yu Kuang; Wei Zou; Xiao-Min Liu; Hong-Bin Lin; Yi Yang (Molecular Biology Reports, 2009)

Inhibition of NFkappaB by activated c-Jun NH2 terminal kinase 1 acts as a switch for C2C12 cell death under excessive stretch - Jiali Tan; Wei Kuang; Zuolin Jin; Fang Jin; Lin Xu; Qiujun Yu; Liang Kong; Guang Zeng; Xiao Yuan; Yinzhong Duan (Apoptosis, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

New norsesquiterpene and sesquiterpene from a soft coral of the genus Nephthea - Ruo-Lin Yang; Yun-Yan Kuang; Jing-Yu Su; Long-Mei Zeng (Natural Product Research, 2008)

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Protective immunity of E. coli-synthesized NS1 protein of Japanese encephalitis virus - Cheng-Wen Lin; Kuang-Ting Liu; Hong-Da Huang; Wei-June Chen (Biotechnology Letters, 2008)

Delimitation of arsenic-contaminated groundwater using risk-based indicator approaches around blackfoot disease hyperendemic areas of southern Taiwan - Cheng-shin Jang; Chen-wuing Liu; Kuang-liang Lu; Ching-chieh Lin (Environmental Monitoring and Assessment, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Coordination between manganese and nitrogen within the ligands in the manganese complexes facilitates the reconstitution of the water-oxidizing complex in manganese-depleted photosystem II preparations - Shuqin Li; Guiying Chen; Guangye Han; Lin Ling; Deguang Huang; A. A. Khorobrykh; S. K. Zharmukhamedov; Qiutian Liu; V. V. Klimov; Tingyun Kuang (JBIC Journal of Biological Inorganic Chemistry, 2006)

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)

Investigation of iodine concentration in salt, water and soil along the coast of Zhejiang, China - Ying-li Lu; Ning-jian Wang; Lan Zhu; Guo-xing Wang; Hui Wu; Lin Kuang; Wen-ming Zhu (Journal of Zhejiang University-SCIENCE B, 2005)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Gene stacking in Phalaenopsis orchid enhances dual tolerance to pathogen attack - Yuan-Li Chan; Kuang-Hung Lin; Sanjaya; Li-Jen Liao; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2005)

Expression studies of mutations underlying Taiwanese Hunter syndrome (mucopolysaccharidosis type II) - Jui-Hung Chang; Shuan-Pei Lin; Shu-Chuan Lin; Kai-Li Tseng; Chia-Ling Li; Chih-Kuang Chuang; Guey-Jen Lee-Chen (Human Genetics, 2005)

Mutational analysis of feedback inhibition and catalytic sites of prephenate dehydratase from Corynebacterium glutamicum - Shih-Kuang Hsu; Long-Liu Lin; Hsueh-Hsia Lo; Wen-Hwei Hsu (Archives of Microbiology, 2004)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

Comparison of soil nitrogen mineralization and nitrification in a mixed grassland and forested ecosystem in central Taiwan - Jeffrey S. Owen; Ming Kuang Wang; Hai Lin Sun; Hen Biau King; Chung Ho Wang; Chin Fang Chuang (Plant and Soil, 2003)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)